Development and Dispersal of Helicoverpa zea (Lepidoptera: Noctuidae) on Non-Bt and Bt Pyramided Cotton. Issue 2 (31st January 2019) - Braswell, Lewis R; Reisig, Dominic D; Sorenson, Clyde E; Collins, Guy D
Abstract: Bollworm ( Helicoverpa zea Boddie) (Lepidoptera: Noctuidae) can cause economic losses in both non-Bt and Bt cotton. Larvae modify their behavior in the presence of Bt by moving away from terminals faster in Bt cotton compared to non-Bt cotton and avoiding Bt-treated diets. Our objectives were to understand differences in bollworm egg and larvae populations within, and dispersal away from, non-Bt and Bt pyramided-toxin cotton. We conducted small plot experiments in 2016 and 2017 to monitor on-plant egg and larval numbers, and off-plant dispersal of larvae, from non-Bt and different Bt toxin pyramided cotton. Bollworm adults preferred to oviposit in most Bt toxin pyramids compared to non-Bt; this was likely unrelated to detection of Bt by adults, but rather density-dependent aversion from high larval populations. First instar numbers were similar in all non-Bt/Bt toxin pyramids and dispersed at a similar rate. Second through fifth instar numbers were higher in non-Bt than Bt toxin pyramids but dispersed equally from all non-Bt/Bt toxin pyramids, regardless of Bt pyramid type. Development times of larvae were often slower in Bt toxin pyramids compared to non-Bt. Fifth instars were found in, and dispersing from, Bt toxin pyramids containing Vip3A, raising concerns of resistance development. Furthermore, differences in oviposition rate among non-Bt/Bt toxin pyramids and slowed development rate of larvae on Bt varieties could create inconsistencies in generation times emerging from Bt and non-Bt hosts, which could contribute to resistance development.